2015
DOI: 10.1063/1.4923377
|View full text |Cite
|
Sign up to set email alerts
|

Hall transport of divalent metal ion modified DNA lattices

Abstract: We investigate the Hall transport characteristics of double-crossover divalent metal ion (Cu2+, Ni2+, Zn2+, and Co2+)-modified DNA (M-DNA) lattices grown on silica via substrate-assisted growth. The electronic characteristics of the M-DNA lattices are investigated by varying the concentration of the metal ions and then conducting Hall measurements, including resistivity, Hall mobility, carrier concentration, and magneto resistance. The tendency of the resistivity and Hall mobility was to initially decrease as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…From Fig 3 , the deep valley demonstrates non-zero current at 0 V for the samples with an offset-shift in the negative direction up to 0.2 and 0.8 V for the 0.036 and 0.18 Gy, respectively. It might be attributed to the alpha particle charge or dose (storage, trapping, and de-trapping of the charge carriers) agreeing with Dugasani et al [ 30 ] and with Reddy et al in terms of the creation of reverse molecule charge interaction between DNA and the metal [ 43 ].…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…From Fig 3 , the deep valley demonstrates non-zero current at 0 V for the samples with an offset-shift in the negative direction up to 0.2 and 0.8 V for the 0.036 and 0.18 Gy, respectively. It might be attributed to the alpha particle charge or dose (storage, trapping, and de-trapping of the charge carriers) agreeing with Dugasani et al [ 30 ] and with Reddy et al in terms of the creation of reverse molecule charge interaction between DNA and the metal [ 43 ].…”
Section: Resultssupporting
confidence: 76%
“…Recently, Dugasani et al observed that the resistivity tendency and Hall mobility declined when the ion concentration was raised while reaching the saturation concentration (C s ) of each metal ion, thereby increasing the ion concentration. Also, they numerically discovered that the metal-DNA lattice behaved as a semiconductor with metal ions through the Hall parameters [ 30 ]. In this current work, we report the study of the current transport characteristics of Au/DNA/ITO Schottky diodes exposed to alpha radiation between 0–0.24 Gy.…”
Section: Introductionmentioning
confidence: 99%
“…DNA can be easily incorporated with nanomaterials possessing their own intrinsic characteristics. Such nanomaterial-embedded DNA hybrid complexes perform specific functions with potential applicability to biosensors and nanoelectronics [83][84][85][86][87][88].…”
Section: Artificially Designed Dna Structuresmentioning
confidence: 99%
“…Among the various nanomaterials such as ions, nanoparticles, carbon-based materials, and proteins, metal ions (e.g., Cu 2+ ) exhibit promising electrical, optical, and magnetic characteristics, which can be helpful in enhancing the DNA characteristics. Although thin films of metal-doped and lanthanide-ion-doped DNA duplexes have been fabricated, hybrid fibers of CDNA metallized with ions synthesized in a large-scale production in a powder form have been rarely discussed. Metal (e.g., Ag, Au, and Pd)-coated DNA nanowires fabricated by chemically derivatized and seeding growth methods were reported; however, the DNA metallization method was complex and the mass production of samples with a high quality was quite limited. CDNA fibers metallized with Cu 2+ are formed as core (CDNA)–shell (Cu 2+ ) structures by self-metallization, which can easily alter the electrical, optical, and magnetic characteristics of the samples.…”
Section: Introductionmentioning
confidence: 99%